(untitled) (Bangladesh Journal of Plant Taxonomy, 2022)
An ethnomedicinal investigation was carried out in Sherpur Sadar and Sreebardi upazilas of Sherpur district to record, and document the traditional knowledge alongside with determining the consensus factor, citation frequency and fidelity level among the folklore medicinal practitioners. A total 51 plant species belonging to 49 genera and 38 families were cited with their mode of application for treating different ailments. The most frequently used plant species were represented by herbs (35.94%) followed by trees (33.33%), shrubs (19.61) and climbers (11.76). Leaves were found to be the most utilized part (50%) followed by root (14%), fruit (10%), flower (10%), stem (10%), bark (4%) and seed (2%). The reported ailments were categorized into 14 diseases and the maximum species were employed to treat digestive and gastrointestinal disorders. Leaves of Eclipta alba (L.) Hassk. are used in treatment of cataract without applying in eyes at the initial stage which is the first report for Bangladesh, and this species could be further screened for bioactive compound which can lead to discovery of new and potential drugs. Many species reported in the current study were found to be very rare which need to be conserved to maximize the sustainable uses of these vital resources in the study area. Bangladesh J. Plant Taxon. 29(2): 269-282, 2022 (December)